Noninvasive Detection of a Balanced Fetal Translocation from Maternal Plasma. (1st October 2014) - Jensen, Taylor J; Kim, Sung K; van den Boom, Dirk; Deciu, Cosmin; Ehrich, Mathias
Abstract: BACKGROUND: Massively parallel sequencing of circulating cell free (ccf) DNA from maternal plasma has been demonstrated to be a powerful method for the detection of fetal copy number variations (CNVs). Although the detection of CNVs has been described by multiple independent groups, genomic aberrations resulting in copy number–neutral events including balanced translocations have proven to be more challenging to detect noninvasively from ccf DNA. METHODS: Data modeling was initially performed to evaluate multiple methods, ultimately leveraging the short length of ccf DNA and paired-end sequencing to construct read-specific mapping characteristics. After testing in a model system, we evaluated the methods on ccf DNA isolated from the plasma of a donor known to be carrying a fetus with a balanced translocation [t(8;11)]. Sequencing was performed with Illumina sequencing technology. RESULTS: Our methodology identified the known translocation ( P = 1.21 × 10 −8 ) and discounted the likelihood of others, enabling the base specific identification of the rearrangement positions. In total, 402 unique sequencing reads spanned the putative breakpoints, of which 76 contained the structural rearrangement. In addition, 38 of the chimeric reads were mapped to each of the resulting derivative chromosomes, supporting the presence of a reciprocal translocation. Finally, we identified a 6-bp deletion present within der(8) that was absent from the der(11) reciprocal rearrangement. CONCLUSIONS: We have developed an algorithm to detect balanced rearrangements and applied our methodology to demonstrate the first proof-of-principle study on the noninvasive detection of a fetal-specific balanced translocation by sequencing ccf DNA from maternal plasma.